A manual for creating atheists - Boghossian, Peter G. (Peter Gregory) (Durham, North Carolina : Pitchstone Publishing, 2013)
Drawing on tools developed by the author, shows readers how to engage the faithful into conversations that lead them to value reason and rationality over their religious beliefs.
Cover; Title Page; Copyright; Dedication; Contents; Foreword; Chapter 1: Street Epistemology; Chapter 2: Faith; Chapter 3: Doxastic Closure, Belief, and Epistemology; Chapter 4: Interventions and Strategies; Chapter 5: Enter Socrates; Chapter 6: After the Fall; Chapter 7: Anti-Apologetics 101; Chapter 8: Faith and the Academy; Chapter 9: Containment Protocols; Acknowledgments; Appendixes; Glossary; References; About the Author; Other Titles from Pitchstone.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 050
Keywords: Atheism; Rationalism; Faith and reason; Religion -- Controversial literature; RELIGION -- Atheism; RELIGION -- Agnosticism; Atheism; Faith and reason; Rationalism; Religion; Atheismus; Atheism; Faith and reason; Rationalism; Religion -- Controversial literature; Electronic books; Controversial literature